The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.3390/molecules27196201
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Nanoparticles of DOX and miR-125b on DNA Damage Repair in Glioma U251 Cells and Underlying Mechanisms

Abstract: Glioma is the most common primary craniocerebral malignant tumor, arising from the canceration of glial cells in the brain and spinal cord. The quality of life and prognosis of patients with this disease are still poor. Doxorubicin (DOX) is one of the most traditional and economical chemotherapeutic drugs for the treatment of glioma, but its toxic effect on normal cells and the resistance of tumor cells to DOX make the application of DOX in the treatment of glioma gradually less effective. To solve this proble… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…However, other studies reported that miR-125b-5p had an oncogenic role in breast cancer by promoting survival and conferring resistance to chemotherapy. For example, miR-125b-5p was found to be upregulated in doxorubicin-resistant breast cancer cells and to inhibit the expression of pro-apoptotic genes [10]. MiR-125b-5p was also found to be downregulated in tamoxifen-resistant breast cancer patients and to be inversely correlated with HER2/neu status [27].…”
Section: Discussion Of Mir-125b Expression and Functionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, other studies reported that miR-125b-5p had an oncogenic role in breast cancer by promoting survival and conferring resistance to chemotherapy. For example, miR-125b-5p was found to be upregulated in doxorubicin-resistant breast cancer cells and to inhibit the expression of pro-apoptotic genes [10]. MiR-125b-5p was also found to be downregulated in tamoxifen-resistant breast cancer patients and to be inversely correlated with HER2/neu status [27].…”
Section: Discussion Of Mir-125b Expression and Functionmentioning
confidence: 99%
“…However, the delivery of miR-125b to breast cancer cells faces several challenges, such as low stability, low cellular uptake, and low target speci city [10]. To overcome these challenges, an e cient and safe delivery system for miR-125b is needed.…”
Section: Introductionmentioning
confidence: 99%
“…Liposomes as drug delivery systems may reduce the negative side effects and increase the therapeutic efficacy. Compared with conventional drugs, liposomes can directly deliver drugs to specific cells or tissues, thereby greatly reducing the adverse effects ( 29 ). In a community-based observational study, Salzberg et al ( 19 ) indicated that PEG-liposomal doxorubicin is a well-tolerated active agent in patients with metastatic breast cancer.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that overexpression of miR-125b enhances the sensitivity of the DOX-resistant breast cancer cell line, MCF-7/R, to DOX and exhibits a similar potential in other tumors, including GBM. Wang et al 80 encapsulated DOX and miR-125b into an amphiphilic co-polymer (γ-PGA-co-PLA-DPPE) containing poly [gamma-glutamic acid (γ-PGA)], polylactide (PLA), and 1,2-dipalmitoyl-sn-glycero-3-phosphoethanolamine (DPPE), and formed co-polymer NPs using a nano-precipitation method. The results showed that miR-125b aggravates cell cycle arrest caused by DNA damage by DOX and activates the AMPK/p53 pathway in U251 cells, thus improving chemosensitivity and promoting tumor cell apoptosis.…”
Section: Nanomedicine-based Combination Therapies To Overcome Drug Re...mentioning
confidence: 99%